Religious Values-Based Role Playing for Character Development in Early Childhood Education: A Case Study at Aisyiyah Bustanul Athfal Kindergarten, Enrekang Regency - Hasrianti Mandalika Hasan; Andi Fitriani Djollong; Muhammad Naim; Suredah Hamid; Nasri Hamang (CV. Gerasi Insan Nusantara, 2026)
Character development in early childhood plays a crucial role in fostering moral, social, emotional, and spiritual competencies that influence children's future behavior and personality. This study aimed to examine the characteristics of early childhood learners, explore the implementation of a religious values-based role-playing method, and identify supporting and inhibiting factors affecting its application in character development at Aisyiyah Bustanul Athfal Kindergarten Dulang, Enrekang Regency, Indonesia. This study employed a descriptive qualitative case study design. Data were collected over a three-month period through observations, in-depth interviews, and documentation involving five key informants consisting of one principal and four classroom teachers. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. Trustworthiness was ensured through credibility, transferability, dependability, and confirmability procedures. The findings revealed that children demonstrated positive character development in creativity, empathy, cooperation, independence, self-confidence, adaptability, honesty, responsibility, tolerance, gratitude, and spiritual awareness. Religious values-based role playing enabled children to actively engage in meaningful learning experiences that integrated Islamic values into daily social interactions. Supporting factors included teacher commitment, parental involvement, collaborative school culture, children's readiness, and appropriate learning materials, while inhibiting factors consisted of limited facilities, time constraints, varying levels of understanding among children, and environmental influences. The study concludes that religious values-based role playing is an effective strategy for promoting holistic character development in early childhood education. Practically, the findings provide guidance for teachers and educational institutions in designing character education programs that integrate religious values through experiential learning activities.